Wood plastic composites (WPCs) from multilayer packaging wastes and rHDPE as pallets for green industry - T Boonsri; S Rukchonlatee; I Jangchud (My University, 2022)
Abstract People are becoming more aware of plastic pollution. Consumers, researchers, and manufacturers are seeking ways to reduce their contribution to the problem. Management of plastic wastes has still been severely environmental problems, especially those with multilayer or multicomponent structures due to the difficulty in recycling process. According to the concept of circular economy, this research aimed to overcome these problems by recycling the multilayer plastic film wastes after use from consumers (classified as post-consumer recycled resin, PCR) and transforming those into high-value products. In this work, Wood Plastic Composites (WPCs) made from mixtures of multilayer packaging wastes (PCRs), recycled high density polyethylene (rHDPE) and wood powders were studied in order to be used as pallets in green industry. Studied factors affecting WPC properties included PCR types (linear low density polyethylene (LLDPE), multilayered oriented polyamide (OPA)/PE and polyethylene terephthalate (PET)/PE films) and rHDPE:PCR weight ratios (40:5, 35:10, 30:15 and 25:20). WPC samples were compounded by a two-roll mill and then shaped into samples by a compression molding machine. Morphological, mechanical and thermal properties of WPCs were examined. From SEM study, it was revealed that wood powders and fibers were well distributed and randomly oriented in WPCs. Both PCRs (OPA/PE and PET/PE) were partially melted because the processing temperatures were below the crystalline melting temperatures of OPA and PET. PCR orientation in WPCs was aligned with the compression direction. Mechanical properties of WPCs from OPA/PE were similar to those of WPCs from PET/PE. WPCs from rHDPE:PCR weight ratios of 40:5 and 35:10 had good mechanical properties which passed the industrial target values. Optimum formulas were then used to form WPC samples by extrusion technique and fabricated into WPC pallets. It was found that the WPC pallets from wastes showed promising properties with high potential to replace conventional pallets in warehouses and industrial transport for green industry.
Keywords: High-density polyethylene; Compression molding; Linear low-density polyethylene; Pallet; Environmental Pollution; Molding (decorative); Wood flour; Blow molding; Microplastics and Plastic Pollution